Neurological impairment and malnutrition in children: The role of home enteral nutrition in real life - Diamanti, Antonella; Capriati, Teresa; Mosca, Antonella; Trovato, Chiara Maria; Laureti, Francesca; Mazzoli, Bianca; Bolasco, Giulia; Caldaro, Tamara; De Peppo, Francesco; Staccioli, Susanna; Papa, Raffaele Edo; Cerchiari, Antonella; et al. (Frontiers in Nutrition, 2023)
Objective: Recent decades have brought an increased survival of children with Neurologic Impairment (NI) but malnutrition and digestive comorbidity remain important challenges to face. We designed the present study to assess the course of nutritional status following standardized Home Enteral Nutrition (HEN) program and to evaluate impact of changing mode of feeding, as a part of overall multidisciplinary management, on digestive co-morbidity as Gastro-Esophageal Reflux Disease (GERD), Oropharyngeal Dysphagia (OPD), constipation and airway aspiration. Methods: We performed a retrospective analysis on NI children entered into Institutional HEN program due to NI disorders between January 2011-2019. Demographic, anthropometric characteristics (BMI z-score and weight for age z-score) and symptoms (GERD, OPD constipation and airway aspiration) were collected at the enrolment and during the follow up. Results: We enrolled 402 patients (median age: 39 months); overall survival was 97%. Nutritional status was significantly improved by HEN; in particular growth profile significantly changed within the first two years following HEN beginning; GERD and airways aspirations decreased after HEN beginning. Constipation and OPD remained unchanged over time. Conclusions: Malnutrition and digestive complaints are distinctive features of NI children. Nutritional status improve after two years from the beginning of standardized nutritional interventions. Overall multidisciplinary care, including standardized HEN protocols, seems to also impact on GERD and airway aspirations, which can decrease over time. It is possible that constipation and OPD, unchanged over time, are more dependent on underlying diseases than on overall treatments.